Income of workers in industrial parks post-COVID-19 pandemic: The raised issues in Vietnam - Thanh Thuy Cu; Tuan Anh Nguyen (Problems and Perspectives in Management)
This study aimed to analyze the adaptation of workers in industrial parks in Vietnam post-COVID-19 through fluctuations in their income. Data were collected from a survey of 438 workers working in industrial parks and in-depth interviews with five workers in different positions in industrial parks. The study utilized the ordinary least squares (OLS) method to quantify the factors influencing workers’ income. Additionally, the difference test method was applied to assess the income variations among workers based on their professional qualifications and occupational skills. The most significant factor identified is the experience of workers (unstandardized coefficient = 0.271), followed by the education level of workers (unstandardized coefficient = 0.128). Additionally, the study reveals that differences in professional qualifications lead to an income disparity of 1.898 million VND per month, while the variations in complementary skills contribute to an income difference of 0.592 million VND per month. Furthermore, the adaptation of workers in Vietnam’s industrial parks post-COVID-19 is at a relatively good level. From there, the study suggests several solutions to enhance workers’ income to adapt to new post-COVID-19 conditions.